The strategic development of maritime connectivity in the border area in Indonesia - Rizaldi, Arjuna; Muzwardi , Ady; Santoso, Edward; Iffan, Muhammad; Fera, Mirta (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Indonesia is an archipelago where eight out of 38 Indonesian provinces are characterized by islands. Thus, the connectivity between islands is substantial in supporting economic development. This research aims to display the possible maritime connection and excavate the obstacles to improving maritime connectivity in the area. This research is qualitative comparative research using the Miles and Huberman model and analyzes it with the Graph Connectivity Node theory, comparing it with actual nodes in the areas and materializing the possible challenge and obstacles in connecting the nodes using RCA and 5 Whys Analysis as the tool. The data is obtained through two ports located in Kepulauan Riau Province. The research finds that the obstacles in connecting the node are infrastructure, budget, and interconnection with other forms of transportation. Therefore, the impact of this research on improving the node lies in the policy to overcome the obstacles encountered.